Advances in CBCT combined with digital technology and artificial intelligence in endodontics - LI Jianing, WANG Shengchao, ZHOU Zichao, ZHANG Qianxia, JIANG Wenkai (Kouqiang yixue)
Oral and maxillofacial CBCT(cone beam computed tomography) as a kind of oral imaging techniques, can accurately show the tooth pulp in an all-round way. Especially for showingthe morphologyof special root canals, it has incomparable advantages over two-dimensional X ray film. With the development of digital technology and artificial intelligence technology, CBCT has been widely used in stomatology. In this paper, we will systematically review the applicationprogress of CBCT combined with oral digital technology and artificial intelligence technology, with a view to providing references for clinical diagnosis and treatmentand technical development of the discipline.